CEO Characteristics and Intellectual Capital Effectiveness: Empirical Evidence from the UK - Adel Necib; Anis Jarboui (Journal of Smart Economic Growth, 2022)
Intellectual capital has been widely studied in the context of broader corporate governance structures. There is little empirical research on CEO relationships. Nevertheless, CEOs have a great responsibility to leverage the intellectual capital that their employees bring to their organisations. Given this gap, this study examines the impact of CEOs on improving a company's intellectual capital. In this study, CEOs are represented by dual CEO status, nationality, gender, seniority, income and ownership, while the Intelligence Value Added Score measures intellectual capital.